2021
DOI: 10.1016/j.jmig.2021.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Adnexal Masses in Pregnancy: A Systematic Review and Meta-analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…These cysts are typically found at prenatal ultrasound check‐ups and operated on if symptoms occur or tumour grows; sometimes, morphology in imaging studies or doctor's and patient's attitudes also encourage surgery 11,12 . In a recent meta‐analysis of ovarian masses operated during pregnancy, the odds ratio (OR) for postoperative spontaneous abortion was similar after elective or emergency surgery (OR 0.26; 95% CI 0.06, 1.02), but OR for preterm delivery was lower (OR 0.13; 95% CI 0.04, 0.48) after elective ovarian surgery than after emergency surgery 13 . This highlights appropriate preoperative evaluation when any surgical interventions are planned in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cysts are typically found at prenatal ultrasound check‐ups and operated on if symptoms occur or tumour grows; sometimes, morphology in imaging studies or doctor's and patient's attitudes also encourage surgery 11,12 . In a recent meta‐analysis of ovarian masses operated during pregnancy, the odds ratio (OR) for postoperative spontaneous abortion was similar after elective or emergency surgery (OR 0.26; 95% CI 0.06, 1.02), but OR for preterm delivery was lower (OR 0.13; 95% CI 0.04, 0.48) after elective ovarian surgery than after emergency surgery 13 . This highlights appropriate preoperative evaluation when any surgical interventions are planned in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 In a recent meta-analysis of ovarian masses operated during pregnancy, the odds ratio (OR) for postoperative spontaneous abortion was similar after elective or emergency surgery (OR 0.26; 95% CI 0.06, 1.02), but OR for preterm delivery was lower (OR 0.13; 95% CI 0.04, 0.48) after elective ovarian surgery than after emergency surgery. 13 This highlights appropriate preoperative evaluation when any surgical interventions are planned in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of surgery during pregnancy on the risk of miscarriage is unclear and the maternal condition necessitating surgery could be the main factor associated with risk of miscarriage and preterm labour ( Cohen-Kerem et al , 2005 ; de Bakker et al , 2011 ; Silvestri et al , 2011 ; Ball et al , 2019 ). The advantages of laparoscopic treatment over open procedures are the reduced risk of postoperative adverse events ( Liu et al , 2017 ) and a shorter hospital stay ( Cagino et al , 2021 ). However, a significantly higher risk of adverse foetal outcomes has been reported following laparoscopic versus open surgery for acute appendicitis ( McGory et al , 2007 ; Wilasrusmee et al , 2012 ; Winter et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, more and more studies show that laparoscopy is a safe and effective surgical approach in pregnancy, providing several advantages over laparotomy, including reduced postoperative pain, analgesic use, and hospitalization time (14). Cagino et al (15) investigated the optimal approach to surgical management of adnexal masses in pregnancy based on a meta-analysis of previous studies. They found that laparoscopy was a safe and effective approach for the surgical management of adnexal masses in pregnancy.…”
Section: Discussionmentioning
confidence: 99%